1134 Light Exposure At Daytime On Sleep Quality In Stroke Patient During Rehabilitation. (27th May 2020) - Liao, W; Lin, S; Meng, N; Tin, H; Tsai, S; Huang, Y
Abstract: Introduction: Lights maintain the day and night rhythm to set patients' "wake-up cycle" and to stabilize their physiological functions, which may be expected to improve sleep. This study was aimed to investigate the relations between sleep quality and daytime light exposure in stroke patient during rehabilitation. Methods: A cross-sectional study design was adopted and 120 stroke patients were recruited from rehabilitation wards of two medical centers and 116 patients completed this study. Research instruments including the Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, Sleep Log, and Somnowatch (Germany) for actigaphy sleep and light were used to collect data and urinary melatonin concentration were measured. Results: 47.4% of the patients had poor sleep quality (PSQI>5), 74.1% had actigraphic sleep efficiency less than 85%, and 90.5% waked more than 30 minutes after sleep onset. The average exposure time at lower level light (≤149 lux) were 288.8 minutes, accounting for 48% of the day (8:00-18:00). Compared to lower light exposure group (less than 319.5 min at >150 lux), those who exposed to higher level light (more than 319.5 min at >150 lux) had increased 52.1 minutes in actigraphic total sleep time (TST, t=-2.134, p=0.035), increased 8% in actigraphic sleep efficiency (SE, t=-2.053, p=0.042), and decreased 41.1 minutes in actigraphic wake-after-sleep-onset (WASO, t=2.209, p=0.029). Urinary melatonin concentration increased 52.7 pg/ml, but not statistically significant (t=-1.277, p=0.205). Result of multiple regression analysis showed that after controlling for age, gender, post-stroke complications, and environmental interference, time of bright light exposure significantly affected subjective sleep satisfaction (p=0.014), TST (p=0.04), SE (p=0.041), and WASO (p=0.026). Conclusion: Increasing time of bright illumination (≥150 lux) during daytime may improve sleep quality. Results of this study provide empirical references for non-drug intervention to improve sleep quality in patients with stroke. Support: This study was supported by the Ministry of Science and Technology, MOST 105-2628-B-040 -005 -MY2.